PENGARUH MODEL PEMBELAJARAN PAIRED STORY TELLING BERBANTUAN BONEKA TANGAN TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS III SD NEGERI 1 MONTONG BELAE KECAMATAN KERUAK - Gea Desta Rini; AriF Rahman Hakim; Yuniar Lestarini; Zalia Muspita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of the Paired Storytelling learning model assisted by hand puppets on Indonesian language learning outcomes of third-grade students at Montong Belae 1 Elementary School. The background of the study is the low speaking skills and learning outcomes of students due to the dominance of the lecture method. The study used a quantitative approach with a One Group Pretest-Posttest design on 24 students. Data were collected through observation and multiple-choice tests that were tested for validity and reliability. The results showed an increase in the average score from 30.75 (pre-test) to 53.875 (post-test), with a difference of 23.125 points. The t-test yielded p < 0.01, indicating a significant effect. In addition to improving cognitive learning outcomes, this model also fosters student engagement, speaking skills, and self- confidence. Thus, paired story telling using hand puppets is effective in improving Indonesian language learning outcomes in elementary schools.